On the sustainable program in solow's model - Cees Withagen; Geir B. Asheim; Wolfgang Buchholz (University of Oslo, Department of Economics, 2002)
We show that our general result (Withagen and Asheim [8]) on the converse of Hartwick's rule also applies for the special case of Solow's model with one capital good and one exhaustible resource. Hence, the criticism by Cairns and Yang [1] of our paper is unfounded.
Keywords: D63; Q01; Q32; 330; Sustainabiliy; maximin path; Harwick's rule; Nachhaltige Entwicklung; Neoklassik; Solow-Modell; Theorie